Human factors as a corporate culture : a thesis presented in partial fulfillment of the requirements for the degree of Master of Aviation at Massey University - Astuti, Dwinarni Wisnu (Massey University, 1997)
Studies on human factors training needs assessment have been conducted within Western airlines. Little, however, is known whether other non-western aviation industries have the same needs. The present study aims to take a small step towards remedying that deficiency. This study concentrates on the identification of specific human factors training which is in line with the organisational objectives, on a sample of Indonesian aviation employees. The needs assessment questionnaire used in this study was based on Hunt's (1984b) NEBEAT model. The questionnaire also obtains biographical information. Descriptive statistics, Principal component analysis, and content analysis were used on the data. A clear implication of the findings of this study is that human factors training is less effective if only received by one of the teams in the company. A corporate culture of human factors is a prerequisite of maximum human resource efficiency and effectiveness.
Keywords: Human factors training; Flight crews; Flight training